1996
DOI: 10.1007/bf00173135
|View full text |Cite
|
Sign up to set email alerts
|

Tribochemistry of ZDDP and MoDDP chemisorbed films

Abstract: By means of a UHV analytical AES/XPS pin-on-flat tribotester, we have investigated tribochemical change as well as transfer mechanisms in static reaction films on steel from ZDDP (anti-wear) and MoDDP (friction modifier) lubricant additives. The results show that solid ZDDP reaction films are able to strongly reduce friction to a value of 0.1-0.3 (in the absence of a film, steel-on-steel gives a friction coefficient value of up to 2). MoDDP reaction films produce ultra-low friction (below 0.05) after an induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 14 publications
(12 reference statements)
1
27
0
Order By: Relevance
“…The binding energies of ZDDP elements found on the wear scar (figure 6 and table 5) show the formation of a phosphate glass [20,21], which is in agreement with the other work [24]. Detection of the S peak showed formation of sulphides whenever ZDDP was used with MoDTC or alone.…”
Section: Effect Of Modtc On Zddp Tribofilm Formationsupporting
confidence: 82%
See 1 more Smart Citation
“…The binding energies of ZDDP elements found on the wear scar (figure 6 and table 5) show the formation of a phosphate glass [20,21], which is in agreement with the other work [24]. Detection of the S peak showed formation of sulphides whenever ZDDP was used with MoDTC or alone.…”
Section: Effect Of Modtc On Zddp Tribofilm Formationsupporting
confidence: 82%
“…It is reported that MoDTC reduces friction by forming a MoS 2 -containing film on the tribological contact [3][4][5][6][7][8]. The layer-lattice structure of the molybdenum disulphide makes it possible for low friction to be achieved between the tribocouple components [9].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, various surface analysis techniques have been used for the characterization of these tribofilms: e.g., Auger electron spectroscopy (AES) [11,12], X-ray photoelectron spectroscopy (XPS) [13][14][15] and X-ray absorption near-edge structure (XANES) spectroscopy in both area averaging and imaging modes [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…11, the EDL is not shown and discussed here. The above hypothesis is formulated on the basis of the knowledge, premises, and predictions [12][13][14][15]. Namely, a short-chain-molecule sublayer just off the metal surface can be the product of a ZDDP reaction with iron (steel).…”
Section: Discussion and Interpretation Of The Resultsmentioning
confidence: 99%
“…3) shows an experimental set-up that consists of: the housing of an oil reservoir (chamber) (1); a seal seating-a metal ring (2); the lip seal tested (3); an insulator (4); the oil tested (5); an air bearing (6); the sensor of a torquemeter (7); an electric motor (8); a steel shaft (9) earthed through the carbon brushes; a microprocessor-based system for controlling the angular velocity n and for measuring the braking torque M b of the shaft and temperature T of oil (10); a standard capacitor C s (11); an electrometer for measuring the ring potential U e (12); a computer (13); a DC power supply U DC (14); and an oil heater (15). The chamber (1) was filled with the oil (5) up to a geometrical axis of the rotating shaft (9).…”
Section: Experimental Set-upmentioning
confidence: 99%